The influence of socioeconomic status and birth weight on blood pressure of Indonesian pre-pubertal children - Madarina Julia; M M van Weissenburch; HA Delemarrevan de Waal; Achmad Surjono (Indonesian Pediatric Society Publishing House, 2016)
Background It has been shown that elevated blood pressure (BP) in childhood contributes to the development of coronary artery disease, cerebrovascular accidents, heart failure, and renal failure in adults. There is also evidence of some correlations between childhood BP and BP in adulthood. Obesity as well as low birth weight are a risk factors for elevated BP, both in children and in adults. Most epidemiological studies have also shown a relationship between high BP and socioeconomic status (SES). Objective To assess the influence of socioeconomic status and birth weight on blood pressure of school-aged prepubertal children living in Indonesia. Methods A cross-sectional survey on 2922 school-aged prepubertal children from the rural, poorurban and nonpoor urban communities was performed. Data on age, sex, stature, BMI, birth weight, systolic and diastolic BP were collected from all children. Results Overall and within every socioeconomic status group, blood pressures were positively associated with stature and body mass index (BMI). Children from poor-socioeconomic families, i.e. rural and poor urban, had significantly lower height and BMI, and hence, in the unadjusted analyses, poor socioeconomic status was associated with lower systolic and diastolic BP. However, after adjustment for age, sex, stature and BMI, rural children were found to have significantly higher systolic BP compared to nonpoor urban children, with regression coefficient (95% CI) of 1.19(0.42 to 1.96). Birth weight was not associated with blood pressure in childhood. Conclusion This study indicated that for a given stature and BMI, poor children had a higher systolic BP